VBTO Simulation: Effect of Dealer Trading and Reconfiguration Flexibility on Performance of Automaker and Its Dealers - Li, Guanghai (2006)
The purpose of this study is to examine the degree to which fulfillment performance is affected by the ability of dealers to trade products, and how reconfiguration flexibility amplifies or diminishes the benefit of trading. The objectives of the study are (a) to identify how trading policy is good to manufacturer, (b) to examine how trading policy impacts dealer's performance and whether it's also good to different dealers, and (c) to illustrate how reconfiguration flexibility has effects on the performance of manufacturer and dealers. Through an intensive literature and practical cases review, some findings of some research efforts on order fulfillment system, simulation methodology and mass customization are introduced. Data were collected via several experiments by running a modified model which is based on a core model, and were analyzed by drawing graphs with data table, and several comparisons made between experiment results. Some implications were given from the experiment results that manufacturer can benefit a lot from dealer trading, performance was improved significantly for instance lead time and stock level, pipe sales percentage as well. Dealer also performed quite good under trading policy, no matter how big they are, reflected by shorter lead time and less stock level. Manufacturer's reconfiguration flexibility has influence on both manufacturer and dealer, the difference of performance between zero and 100% reconfiguration flexibility is remarkable. However, experiments under 50% reconfiguration flexibility give very interesting results, it seems to encourage manufacturer to try to get dealers involved in trading products, other than try to increase reconfiguration flexibility.